The effect of cingulate lesions on social behaviour and emotion. - Hadland, K; Rushworth, M; Gaffan, D; Passingham, R (2003)
Functional and structural neuroimaging of the human cingulate cortex has identified this region with emotion and social cognition and suggested that cingulate pathology may be associated with emotional and social behavioural disturbances. The importance of the cingulate cortex for emotion and social behaviour, however, has not been clear from lesion studies. Bilateral lesions in the cingulate cortex were made in three macaques and their social interactions were compared with those of controls. Subsequently, cingulate lesions were made in the three controls and their behaviour was compared before and after surgery. Cingulate lesions were associated with decreases in social interactions, time spent in proximity with other individuals, and vocalisations but an increase in manipulation of an inanimate object. The results are consistent with a cingulate role in social behaviour and emotion.